IQBAL: A CRITIC OR A DEFENDER OF SUFISM? (Al-Aasar, 2025)
Allama Muhammad Iqbal, a celebrated political leader, philosopher and scholar of Islam, is considered the national poet of Pakistan. He belonged to a religious family which was spiritually affiliated with Sufism. The place of Sufism in Islam has always remained a controversial question in the history of Islam. The question regarding the compatibility of Islam and Sufism and the place of Sufism in Islam was raised afresh with the advent of modernity in the nineteenth and twentieth centuries. Iqbal attempted to reconcile Sufism with rational-scientific knowledge and tried to address this issue by challenging the traditional sufi conception. He advocated the need to reform the institution of Sufism. He considered it compatible with Islam but rejected the un-Islamic practices amalgamated in the institution. Iqbal never engaged in a wholesale rejection of Sufism per se as an ideology, but he criticized some of the sufi doctrines and practices, which include un-Islamic influences, hereditary succession, commercialization of khanqahs, and the ideal of asceticism or world-renunciation. In fact, Iqbal propagated the idea of “Reformed Sufism,” which refers to the kind of Sufism which is shariah-oriented, and has the ability to reconcile with modernity, and contribute to moral reconstruction of the society. His idea of reformed Sufism entailed the concept of ‘ego’ or khudi, determination, dynamism, optimism and hopefulness.